On the superposition of mean advective and eddy-induced transports in global ocean heat and salt budgets - Boeira Dias, FB; Domingues, CM; Marsland, SJ; Griffies, SM; Stephen Rintoul; Matear, R; Fiedler, R (2020)
Ocean thermal expansion is a large contributor to observed sea level rise, which is expected to continue into the future. However, large uncertainties exist in sea level projections among climate models, partially due to intermodel differences in ocean heat uptake and redistribution of buoyancy. Here, the mechanisms of vertical ocean heat and salt transport are investigated in quasi-steady-state model simulations using the Australian Community Climate and Earth-System Simulator Ocean Model (ACCESS-OM2). New insights into the net effect of key physical processes are gained within the superresidual transport (SRT) framework. In this framework, vertical tracer transport is dominated by downward fluxes associated with the large-scale ocean circulation and upward fluxes induced by mesoscale eddies, with two distinct physical regimes. In the upper ocean, where high-latitude water masses are formed by mixed layer processes, through cooling or salinification, the SRT counteracts those processes by transporting heat and salt downward. In contrast, in the ocean interior, the SRT opposes dianeutral diffusion via upward fluxes of heat and salt, with about 60% of the vertical heat transport occurring in the Southern Ocean. Overall, the SRT is largely responsible for removing newly formed water masses from the mixed layer into the ocean interior, where they are eroded by dianeutral diffusion. Unlike the classical advective–diffusive balance, dianeutral diffusion is bottom intensified above rough bottom topography, allowing an overturning cell to develop in alignment with recent theories. Implications are discussed for understanding the role of vertical tracer transport on the simulation of ocean climate and sea level.